2022
DOI: 10.1038/s41467-021-27512-0
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl chain translocation catalysed by a type II thioesterase domain in an unusual non-ribosomal peptide synthetase

Abstract: Non-Ribosomal Peptide Synthetases (NRPSs) assemble a diverse range of natural products with important applications in both medicine and agriculture. They consist of several multienzyme subunits that must interact with each other in a highly controlled manner to facilitate efficient chain transfer, thus ensuring biosynthetic fidelity. Several mechanisms for chain transfer are known for NRPSs, promoting structural diversity. Herein, we report the first biochemically characterized example of a type II thioesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Thioesterase (TE) domains are α/β-hydrolases that commonly appear in NRPS assembly lines and catalyze a variety of reactions on T-domain PPant-tethered peptidyl thioester substrates, including hydrolysis, epimerization, transacylation, lactamization, and lactonization. , Type I TE-domains (TEI) are frequently present in NRPS terminating modules, where they catalyze the hydrolytic release of peptides often via macrolactamization or macrolactonization to give cyclic peptide and depsipeptide products, respectively. , Type II TE-domains (TEII) are less common and occur as standalone domains that act in trans on T-domain thioester substrates. Standalone TEII domains have been shown to facilitate acyl transfer between T-domains in NRPS modules, but that does not seem to be an essential function for FbsM, given that the NRPS machinery FbsEFGH is capable of fimsbactin A production in the absence of FbsM. Under our in vitro conditions, the apparent rate of fimsbactin A formation via chemoenzymatic synthesis by FbsEFGH from DHB, L-Ser, and ahPutr was not obviously enhanced in the presence of FbsM, arguing against a kinetic role facilitating inter- and intrachain acyl transfers (Figure S7).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thioesterase (TE) domains are α/β-hydrolases that commonly appear in NRPS assembly lines and catalyze a variety of reactions on T-domain PPant-tethered peptidyl thioester substrates, including hydrolysis, epimerization, transacylation, lactamization, and lactonization. , Type I TE-domains (TEI) are frequently present in NRPS terminating modules, where they catalyze the hydrolytic release of peptides often via macrolactamization or macrolactonization to give cyclic peptide and depsipeptide products, respectively. , Type II TE-domains (TEII) are less common and occur as standalone domains that act in trans on T-domain thioester substrates. Standalone TEII domains have been shown to facilitate acyl transfer between T-domains in NRPS modules, but that does not seem to be an essential function for FbsM, given that the NRPS machinery FbsEFGH is capable of fimsbactin A production in the absence of FbsM. Under our in vitro conditions, the apparent rate of fimsbactin A formation via chemoenzymatic synthesis by FbsEFGH from DHB, L-Ser, and ahPutr was not obviously enhanced in the presence of FbsM, arguing against a kinetic role facilitating inter- and intrachain acyl transfers (Figure S7).…”
Section: Results and Discussionmentioning
confidence: 99%
“…FbsL is a predicted phosphopantetheinyl transferase (PPTase) presumably required for priming the acyl carrier domains with the needed phosphopantetheinyl (PPant) prosthetic thiol group . FbsM is a predicted type II thioesterase (TEII) that might serve an editing, shunting, and/or acyl transfer function . FbsH is predicted to be a standalone adenylation (A 1 ) domain with selectivity for DHB as the substrate.…”
Section: Introductionmentioning
confidence: 82%
“… 21 TEIIs perform housekeeping functions and maintain operation of the NRPS assembly line through various actions ( Figure 1 C). 22 , 23 The need for TEIIs arises, for instance, from the sloppy action of phosphopantetheine transferases (PPTases) mispriming T-domains with already acylated coenzyme A (CoA). Several studies show a significant decrease in product yield after deletion of TEII genes.…”
mentioning
confidence: 99%
“…The presence of a conserved motif (GHSXG) suggests type II thioesterase (TEII) activity . TEIIs perform housekeeping functions and maintain operation of the NRPS assembly line through various actions (Figure C). , The need for TEIIs arises, for instance, from the sloppy action of phosphopantetheine transferases (PPTases) mispriming T-domains with already acylated coenzyme A (CoA). Several studies show a significant decrease in product yield after deletion of TEII genes. , While TEIIs are widespread in NRPS pathways, their impact on engineered systems has not been systematically investigated.…”
mentioning
confidence: 99%
“…batD, which encoded a standalone thioesterase (type II thioesterase), was found next to batC, and two recent studies showed that a type II thioesterase was involved in the translocation of substrates. 30,31 Herein, we proposed the type II thioesterase BatD translocated the pentapeptidyl substrates onto the PCP domain of the second Cy domain-embedded modules of BatC. This resulted in the incorporation of the third thiazole ring into the scaffold, and the substrate was then off-loaded by either cyclization to yield compounds 1 and 3−5 or hydrolysis to yield compound 7.…”
mentioning
confidence: 99%